Modication of gold active layer for detection cobalt ion via surface plasmon resonance spectroscopy - Saleviter, Silvan; Yap, Wing Fen; Sheh Omar, Nur Alia; Mohd Daniyal, Wan Mohd Ebtisyam Mustaqim (2018)
In this study, gold layer has been modified by introducing chitosan-graphene oxide-cadmium sulfide quantum dots on the gold layer for the detection of cobalt ion, Co2+. The composite material was deposited on the gold layer by using spin coater machine. The thin film was used as an active layer for the detection of Co2+ using surface plasmon spectroscopy and the optical changes of the thin film after contacting with different concentration of Co2+ ions had been obtained and graph fitted. The resonance angle shifted to a higher value as the concentration of Co2+ ions was increased. Changes of the resonance angle showed that Co2+ ion does react with the modified thin film with a binding affinity of 3.03 M-1.